Phase 2 Multicenter Study of Gantry-Based Stereotactic Radiotherapy Boost for Intermediate and High Risk Prostate Cancer (PROMETHEUS) - Pryor, David; Sidhom, Mark; Arumugam, Sankar; Bucci, Joseph; Gallagher, Sarah; Smart, Joanne; Grand, Melissa; Greer, Peter; Keats, Sarah; Wilton, Lee; Martin, Jarad (Frontiers in Oncology, 2019)
Objectives: To report feasibility, early toxicity, and PSA kinetics following gantry-based, stereotactic radiotherapy (SBRT) boost within a prospective, phase 2, multicenter study (PROMETHEUS: ACTRN12615000223538). Methods: Patients were treated with gantry-based SBRT, 19–20 Gy in two fractions delivered 1 week apart, followed by conventionally fractionated IMRT (46 Gy in 23 fractions). The study mandated MRI fusion for RT planning, rectal displacement, and intrafraction image guidance. Toxicity was prospectively graded using the Common Terminology Criteria for Adverse Events version 4.0 (CTCAE v4). Results: Between March 2014 and July 2018, 135 patients (76% intermediate, 24% high-risk) with a median age of 70 years (range 53–81) were treated across five centers. Short course (≤6 months) androgen deprivation therapy (ADT) was used in 36% and long course in 18%. Rectal displacement method was SpaceOAR in 59% and Rectafix in 41%. Forty-two and ninety-three patients were treated at the 19 Gy and 20 Gy dose levels, respectively. Median follow-up was 24 months. Acute grade 2 gastrointestinal (GI) and urinary toxicity occurred in 4.4 and 26.6% with no acute grade 3 toxicity. At 6, 12, 18, 24, and 36 months post-treatment the prevalence of late grade ≥2 gastrointestinal toxicity was 1.6, 3.7, 2.2, 0, and 0%, respectively, and the prevalence of late grade ≥2 urinary toxicity was 0.8, 11, 12, 7.1, and 6.3%, respectively. Three patients experienced grade 3 late toxicity at 12 to 18 months which subsequently resolved to grade 2 or less. For patients not receiving ADT the median PSA value pre-treatment was 7.6 ug/L (1.1–20) and at 12, 24, and 36 months post-treatment was 0.86, 0.36, and 0.20 ug/L. Conclusions: Delivery of a gantry-based SBRT boost is feasible in a multicenter setting, is well-tolerated with low rates of early toxicity and is associated with promising PSA responses. A second transient peak in urinary toxicity was observed at 18 months which subsequently resolved. Follow-up is ongoing to document late toxicity, long-term patient reported outcomes, and tumor control with this approach.